2016
DOI: 10.1021/jacs.5b12687
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Trioxacarcins DC-45-A1, A, D, C, and C7″-epi-C and Full Structural Assignment of Trioxacarcin C

Abstract: Trioxacarcins DC-45-A2, DC-45-A1, A, D, C7″-epi-C, and C have been synthesized through stereoselective strategies involving BF3·Et2O-catalyzed ketone-epoxide opening and gold-catalyzed glycosylation reactions, and the full structural assignment of trioxacacin C was deciphered via the syntheses of both of its C7″ epimers. The gathered knowledge sets the foundation for the design, synthesis, and biological evalution of analogues of these natural products as potential payloads for antibody-drug conjugates and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Extensive mechanistic studies have been performed on the reaction, which supports a mechanism shown in Scheme . The utility of this protocol has been demonstrated by its applications in the total syntheses of natural products including periploside A, acremomannolipin A, and trioxacarcins …”
Section: Transition Metal Catalysismentioning
confidence: 62%
“…Extensive mechanistic studies have been performed on the reaction, which supports a mechanism shown in Scheme . The utility of this protocol has been demonstrated by its applications in the total syntheses of natural products including periploside A, acremomannolipin A, and trioxacarcins …”
Section: Transition Metal Catalysismentioning
confidence: 62%
“…Next, we screened various Lewis or Brønsted acids to install the bridged acetal group via a ring opening/acetalation process. We found that SnCl 4 59 , 60 smoothly catalyzed this tandem process and led to the formation of 95 in 85% yield. Subsequent CAN oxidation afforded oncocalyxone B ( 6 ) in 92% yield; 1 H and 13 C nuclear magnetic resonance (NMR) spectra and high-resolution mass spectrometry data for this synthetic compound were fully consistent with those of the natural product 14 , 15 .…”
Section: Resultsmentioning
confidence: 87%
“…Between 2015 and 2017, the Nicolaou group [89,90,91] developed the elegant divergent total synthesis of five highly potent cytotoxic agents trioxacarcins DC-45-A1, DC-45-A2, A, C, and D from a common trioxacarcin precursor 119 , which was efficiently constructed using asymmetric organocatalytic epoxidation as one of the most versatile strategies (Scheme 32).…”
Section: Asymmetric Total Synthesis Of Bioactive Natural Products mentioning
confidence: 99%